Classificação de cônicas e quádricas - Oyafuço, Keide Tukamoto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The main objective of this study is to classify the conics curves and the quadrics surfaces that are represented through equations Ax2 + By2 + Cz2 + Dxy + Exz + Fyz + Gx + Hy + Iz + J = 0 whit A,B,C,D,E.F,G,H, I, J 2 R. Before the classification of these curves and surfaces we will present some concepts and results of Linear Algebra such as the vector spaces with an inner product, adjoints operators and the bilinear forms. The concepts and results presented will be the supported for the classification of the conics as of the quadrics. Beyond the classification of the conics and the quadrics, we go to present a proposal of activity with software GEOGEBRA so that students of Ensino Médio better understand the concept of the conics (ellipse, hyperbola and parabola)

O principal objetivo deste estudo é classificar as curvas cônicas e as superfícies quádricas que são representadas através de equações do tipo Ax2 + By2 + Cz2 + Dxy + Exz + Fyz + Gx + Hy + Iz + J = 0, com A,B,C,D,E.F,G,H, I, J 2 R. Antes da classificação dessa curvas e superficies vamos apresentar alguns conceitos e resultados dentro da Álgebra Linear como os espaços vetoriais com produto interno, operadores adjuntos e as formas bilineares. Os conceitos e resultados apresentados servirão de suporte à classificação tanto das cônicas como das quádricas. Além da classificação das cônicas e das quádricas, vamos apresentar uma proposta de atividade com o software GEOGEBRA para que alunos do Ensino Médio entendam melhor o conceito das cônicas (elipse, hipérbole e parábola)
Keywords: Matemática - Estudo e ensino; Geonetria - Estudo e ensino; Seções cônicas; Quadricas; Tecnologia educacional; Ensino auxiliado por computador